White whales (Delphinapterus leucas) from three Alaskan stocks: Concentrations and patterns of persistent organochlorine contaminants in blubber - Krahn, MM; Burrows, D.G.; Stein, J.E.; Becker, P.R.; Schantz, M.M.; Muir, D.C.G.; O'Hara, T.M.; Rowles, T. (J. Cetacean Res. Manage., 1999)
White whale (De!phinapterus leucas) blubber samples from three of the five different Alaskan stocks, Cook Inlet (n = 20), Eastern Chukchi Sea (n = 19) and Eastern Beaufort Sea (n = 2), were analysed for levels and patterns of chemical contaminants. Blubber from these whales contained LPCBs, LDDTs, Lchlordanes, HCB, dieldrin, mirex, Ltoxaphene and LHCH, generally in concentration ranges similar to those found in white whales from the Canadian Arctic but lower than those in white whales from the highly contaminated St Lawrence River. Males from the Cook Inlet and Eastern Chukchi Sea stocks had higher mean concentrations of all contaminant groups than females of the same stock, a result attributable to the transfer of these organochlorine contaminants (OCs) from the mother to the calf during pregnancy and lactation. Principal component analysis of patterns of contaminants present in blubber showed that the Cook Inlet stock appeared to have identifiable contaminant patterns that allowed the stock to be distinguished from the others. Our results also showed that blubber from the three Alaskan stocks was a source of contaminant exposure for human subsistence consumers, but the health risks from consumption are currently unknown.